Characterisation, cloning and heterologous expression of the α-glucuronidase from Aureobasidium pullulans - De Wet, Barend Johannes Marthinus (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2004.